Simplified indexes for the seismic assessment of masonry buildings : international database and validation - Lourenço, Paulo B. (2013)
Heritage masonry buildings are particularly vulnerable to earthquakes because they are deteriorated and damaged, they were built with materials with low resistance, they are heavy and the connections between the various structural components are often insufficient. The present work details a simplified method of seismic assessment of large span masonry structures that was applied to a database of forty-four monuments in Italy, Portugal and Spain, providing lower bound formulas for different simplified geometrical indexes. Subsequently, the proposed thresholds are validated with data from the 2010-2011 Canterbury earthquakes, which includes forty-eight stone and clay brick masonry churches. Finally, fragility curves that can be used to estimate the damage as a function of the peak ground acceleration (PGA) are also provided.